The intercultural relations as a main factor of intercultural social capital for socio-economic development in multicultural societies. The research example of Trieste, Italy. - Bitsani, Eugenia (Archives of Business Research, 2014)
Abstract The present paper is based on extensive research, titled ““Administration of social services in multicultural societies, contemporary approaches of the intercultural relations and intercultural communication: The case of Trieste in Italy and Thessalonica in Greece”. within the framework of co-operation with the University of Aquila Italy. The present study, by exploring the intercultural social capital and intercultural relations within the city, aims to highlight the qualitative characteristics of this social capital and these relations, by assessing and interpreting them. Over the past few years the global community has been experiencing a hail of changes in all areas of the political, economic, and social activity and every nation is making heroic efforts to maintain its quality of life at a high standard. The magnanimous financial crisis, the political parties, the new social-political movements, the perceptions concerning self-management and the increasing process of globalization have “wiped –out’ the welfare state and have undermined the entire social welfare system on an international scale, a fact which appoints the social capital and the networks as countervailing entities of major importance, entities that actually support the socio-economic development and social cohesion, as well. Migration, which leads to the formation of cultural minorities, is defined as one of the main culprits of social exclusion at an individual and group level. At a social level, national and cultural differences, which are constantly spiraling, owing to international migration, are recognized as one of the main structural changes taking place not only in the societies of the European Union, but also all around the world. The research results showed that the cultural diverse groups get close to each other and form networks based upon their cultural characteristics. Also, it was shown that the intercultural relationships development and encouragement by the local authorities lead to the construction of a strong social capital, which is necessary for the socio-economic development and social cohesion. Key words Intercultural relations, economic crisis, social economy, social enterprises, intercultural social networks, local development.